PEMBUKTIAN UNSUR PERSAMAAN PADA POKOKNYA DAN ITIKAD TIDAK BAIK DALAM UPAYA PEMBATALAN MEREK TERDAFTAR - Arnold Arnold; Marni Emmy Mustofa; Basuki Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Legal protection for trademarks in Indonesia still faces problems with trademark registration in bad faith that have substantial similarity with other parties' marks. The fundamental problem lies in the absence of clear objective parameters for determining the criteria of substantial similarity and bad faith, creating legal uncertainty in trademark cancellation efforts. This research examines two issues: first, what are the criteria for proving substantial similarity and bad faith in trademark cancellation cases; second, what is the ideal regulatory concept for proving these elements to strengthen legal certainty. The research employs theories of evidence, legal protection, and legal certainty and justice to analyze Supreme Court Decision Number 123 K/Pdt.Sus-HKI/2023 regarding the cancellation of